(untitled) (Herald of the National Children’s Medical Center, 2025)
Operative treatment of urinary nai defects in pediatric patients presents a specific challenge, especially in cases where there is a recurrence obstruction and a deficiency in the length of the urinary nai. In this study, a reconstruction of the urethra using a worm tumor (appendix) was carried out, and the effectiveness and possibility of application of this method was shown.